Influence of thermal aging on mechanical properties of fiber metal laminates hybridized with nanoclay. (October 2019) - Najafi, Moslem; Ansari, Reza; Darvizeh, Abolfazl
One of the main problems of polymer matrix composites in critical applications is their high sensitivity to thermal conditions. Therefore, an experimental study was performed to evaluate the thermal durability of traditional plain weave E-glass/epoxy as well as fiber metal laminates as a possible alternative in this case. In this way, both the laminate types were exposed to thermal aging at 130 ℃ for five weeks, and the plausible degradation is investigated through weight loss analyzes and mechanical testing. The possibility of improving the mechanical behavior of the studied laminates by nanoclay was also studied. The results demonstrated that the weight loss and mechanical degradation were more pronounced in thermally aged plain weave E-glass/epoxy composites. The results also indicated that nanoclay could enhance the mechanical properties of both laminates. On the basis of the results, the shielding role of aluminum layers and thermal resistance of nanoclay can synergistically offer a novel class of nano-fiber metal laminates with high thermal tolerance in thermo-oxidative conditions.